PRIMER OPTIMIZATION AS GENETIC MARKER PRIMER BASED ON CYTOCHROME B GENE ON SUMATRAN ELEPHANT (Elephas maximus sumatranus) NON-INVASIVE SAMPLES - Eko Agus Srihanto; Elly Lestari Rustiati; Priyambodo Priyambodo; Dian Neli Pratiwi; Alvin Wiwiet Susanto; Diah Esti Anggraini; Enny Saswiyanti (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Sumatran elephant is declared as critically endangered by IUCN since 2011. In supporting conservation efforts on sumatran elephant in its natural habitat, molecular data collection of their population needs to be done. Genetic source material is mostly obtained in its natural habitat is its dung/feces. Study on cytochrome B gene as genetic marker from sumatran elephant fecal samples can be done to get additional genetic data as a form of conservation effort. Primer optimization as genetic marker based on cytochrome B gene has been carried out as an early study on sumatran elephant genetics. Primer optimization program based on cytochrome B genetic marker from sumatran elephant fecal samples was under Higher Education Applied Research funded by The Ministry of Research, Technology, and Higher Education. DNA was isolated from fecal samples of captive sumatran elephants in Elephant Training Center, Way Kambas National Park. Primer optimization was done via amplification by increasing certain temperature. Specificity test was done to ensure that the primer only recognized sumatran elephant DNA. The best result was obtained with the annealing temperature of 52oC